Exploring the computational thinking of our pre-service mathematics teachers in prepare of lesson plan - Maharani, Swasti; Nusantara, Toto; As'ari, Abdur Rahman; Qohar, Abd (Journal of physics. Conference series, 2021)
Computational thinking is indispensable to face the challenges of the 21st century, including education. Recently there are a lot of issues about the inclusion of computational thinking in the curriculum in Indonesia. Of course, this requires teachers in Indonesia to understand and apply computational thinking. One example of the application of computational thinking by the teacher is in preparing lesson plans. The purpose of this study is to analyze computational thinking in pre-service mathematics teachers in preparing lesson plans. Using qualitative methods, the subjects in this study were six pre-service mathematics teachers. The analysis is done by observing the steps taken by the subject in preparing lesson plans and conducting in-depth interviews to reveal the subject's computational thinking. The results revealed that generalizations were less visible in the preparation of lesson plans for pre-service mathematics teachers. Some teachers are not coherent in preparing lesson plans, due to lack of understanding of the usefulness of the lesson plans that are prepared. The findings of this study are that CT pre-service teachers can be classified into four types, namely full CT, less full CT, unfull CT, and non-CT. Suggestions or recommendations for further research are analyzing teachers who lack understanding about the preparation of the lesson plan, what the obstacles are, and how the solutions for it.